DEMOKRASI PENDIDIKAN ISLAM DALAM MENYONGSONG ERA VUCA (VOLATILITIY UNCERTAINTY COMPLEXITY AND AMBIGUITY) - Surawardi Surawardi; Siti Wardah; Mariam Maila Ramadhani; Lia Lia; Ahmad Noor Saipillah; Muhammad Goezali Hamid (Program Studi PAI STAI Al Falah Banjarbaru, 2025)
AbstractAbstract Islamic education faces major challenges in realizing the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity). This era demands education to be more adaptive and responsive to rapid and uncertain changes. In this context, Islamic educational democracy becomes important because it allows active participation from all stakeholders in the educational process. By implementing the principles of democracy, Islamic education can improve the quality and relevance of its education, so that its graduates are better prepared to face challenges in the VUCA era. This study aims to explore how Islamic educational democracy can be implemented in welcoming the VUCA era. Through context analysis and case studies, this study found that Islamic educational democracy can facilitate a more inclusive and participatory learning process. This allows students to develop critical, creative, and collaborative skills that are much needed in the VUCA era. Thus, Islamic education can play a more effective role in preparing a future generation that is more adaptive and ready to face the complexities of the modern world. Keywords: Islamic Education Democracy, Vuca Era AbstrakPendidikan Islam menghadapi tantangan besar dalam mewujudkan era VUCA (Volatility, Uncertainty, Complexity, dan Ambiguity). Era ini menuntut pendidikan untuk lebih adaptif dan responsif terhadap perubahan yang cepat dan tidak pasti. Dalam konteks ini, demokrasi pendidikan Islam menjadi penting karena memungkinkan partisipasi aktif dari semua pemangku kepentingan dalam proses pendidikan. Dengan menerapkan prinsip demokrasi, pendidikan Islam dapat meningkatkan kualitas dan relevansi pendidikannya, sehingga lulusannya lebih siap menghadapi tantangan di era VUCA. Penelitian ini bertujuan untuk mengeksplorasi bagaimana demokrasi pendidikan Islam dapat diimplementasikan dalam menyongsong era VUCA. Melalui analisis konteks dan kajian kasus, penelitian ini menemukan bahwa demokrasi pendidikan Islam dapat memfasilitasi proses pembelajaran yang lebih inklusif dan partisipatif. Hal ini memungkinkan siswa untuk mengembangkan kemampuan kritis, kreatif, dan kolaboratif yang sangat dibutuhkan di era VUCA. Dengan demikian, pendidikan Islam dapat berperan lebih efektif dalam mempersiapkan generasi masa depan yang lebih adaptif dan siap menghadapi kompleksitas dunia modern. Kata kunci: Demokrasi Pendidikan Islam , Era Vuca